Implementasi Finate State Machine Pada Game Save World Sebagai Pengantar Pembelajaran Geografi - Syaivi Indra Giri; Iwan Rizal Setiawan; Lelah Lelah (STMIK KAPUTAMA, 2020)
ABSTRACK Games are one of the entertainment facilities that are in great demand, both children and adults. The development of information technology is increasingly inevitable because the development of increasingly advanced times and the development of games lately is increasingly rapid. The game that will be created will take the title